2009
DOI: 10.1189/jlb.0109012
|View full text |Cite
|
Sign up to set email alerts
|

Kinin B1 receptor activation turns on exocytosis of matrix metalloprotease-9 and myeloperoxidase in human neutrophils: involvement of mitogen-activated protein kinase family

Abstract: During neutrophil activation and degranulation, MMP-9 and MPO are released into the extracellular space to propagate inflammatory disorders. As kinin peptides are major participants in acute inflammatory responses, and the G-protein-coupled B(1)R mediates the chemotaxis of human neutrophils, we examined the release of the neutrophil enzymes MMP-9 and MPO by the B(1)R agonist LDBK and determined the signaling pathways that may regulate this cellular effect. Cytochalasin-treated and -untreated neutrophils were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 43 publications
4
37
0
Order By: Relevance
“…It is reported that the activated NF-kB by TNF-a could directly interact with the promoter region of the human MMP-9 gene (44). p38 MAPK is closely involved in the expression of MMP-9, MPO, superoxide, and elastase in neutrophils or B-CLL cells (45)(46)(47)(48). Thus, we conclude that the enhanced function of Wip1-deficient neutrophils may be mainly mediated by the increased p38 MAPK-STAT1 and NF-kB pathways.…”
Section: Discussionmentioning
confidence: 72%
“…It is reported that the activated NF-kB by TNF-a could directly interact with the promoter region of the human MMP-9 gene (44). p38 MAPK is closely involved in the expression of MMP-9, MPO, superoxide, and elastase in neutrophils or B-CLL cells (45)(46)(47)(48). Thus, we conclude that the enhanced function of Wip1-deficient neutrophils may be mainly mediated by the increased p38 MAPK-STAT1 and NF-kB pathways.…”
Section: Discussionmentioning
confidence: 72%
“…Previous studies have shown that thrombin causes the release of various enzymes from human neutrophils, including elastase, at the moment at which they attach to the endothelium (Toothill et al, 1990). Recently, we have shown that stimulation of human neutrophils with the natural B 1 R ligand results in the release of matrix metalloproteinase-9 (MMP-9) by a mechanism that depends on the phosphorylation of ERK1/2 and p38 MAPK in a cascade that involves protein kinase C and phosphoinositide-3 kinase (Ehrenfeld et al, 2009). MMP-9 is an extensively glycosylated enzyme, abundantly expressed in tertiary granules of human neutrophils, and is considered a key enzyme that degrades type-IV collagen, the major protein component of basement membranes that provide the molecular network support for endothelial cells.…”
Section: Inflammation and Neutrophil Functionmentioning
confidence: 99%
“…MPO may contribute to plaque destabilization through the activation of MMPs and inactivation of their inhibitors, resulting in degradation of the fibrous cap matrix. Activation of human neutrophils can result in the simultaneous release of MPO and active MMP-9 [86], suggesting that MPO may activate MMPs upon degranulation. Indeed, low concentrations of HOCl have been reported to directly activate MMP-7 in vitro by oxidation of the thiol moiety of the MMP cysteine switch domain [57].…”
Section: Activation Of Matrix Mmpsmentioning
confidence: 99%